Improving the Visual-Spatial Intelligence snd Results of Learning of Juniour High School Students’ with Multiple Intelligences-Based Students Worksheet Learning on Lens Materials - Gani, A.; Safitri, R.; Mahyana, M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
This research is done for the development of students’ worksheet (LKPD) about multiple intelligences-based lens materials for improving the students’ visual-spatial intelligence and results of learning of SMP N 2 Banda Aceh. This research uses a quasi-experimental design with pretest and posttest group. The sampling was done by purposive sampling technique. The data collection was conducted with pretest and posttest for visual-spatial intelligence and learning outcomes. The questionnaire was used to determine the response of students after using students’ worksheet based on multiple bits of intelligence. The results of normality and homogenity test show that the data was homogen and normally distributed. Therefore, the average difference test against the N-gain visual-spatial intelligence and learning outcomes between the two classes used t test and obtained a significant difference in learning outcomes between the two classes. The average score of the N-gain visual-spatial intelligence and learning outcomes for both classes was in the middle category, where the experimental class is 0.65 (65%), while for class gained control is 0.46 (46%). Learners gave a positive response to the use of multiple intelligences-based students’ worksheet dealing with lens materials that can enhance their visual-spatial intelligence and learning outcomes.